Comparative Study of Student Learning Outcomes in Online and Offline Learning during the Pandemic - Putri Ulfa Kamalia; Norida Canda Sakti; Riza Yonisa Kurniawan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Learning is carried out offline starting April 2022 after the COVID-19 pandemic began to subside and the statistics on COVID-19 cases in the city of Surabaya showed a low risk status. Learning that was originally done online was changed back to being done offline. Therefore, this study aims to identify differences in student learning outcomes in online and offline learning. This research is a quasi-experimental research with comparative method and quantitative approach. Research data was collected on macroeconomic theory courses in the even semester of the 2020/2021 academic year for online learning and the 2021/2022 school year for offline learning. The study population was 18 students who were randomly selected from the economic education study program in 2020 and 2021. Processing and analysis of research data used an independent sample T-test. Based on the results of the independent sample t-test, the Sig (two-sided) value is 0.356 > 0.05. These results indicate that there is no significant difference in the average student learning outcomes between online and offline learning. Students' online learning has an average learning outcome of 85.8889, higher than offline learning of 81.3333. Therefore, learning activities are more flexible during the pandemic and can be done online or offline.